Carbon-coated NiMn layered double hydroxides/Ni3S2 nanocomposite for high performance supercapacitors. (September 2021) - He, Yezeng; Liu, Didi; Zhao, Houqiang; Wang, Jiemei; Sui, Yanwei; Qi, Jiqiu; Chen, Zheng; Zhang, Ping; Chen, Changjiu; Zhuang, Dongdong
Highlights: The C/NiMn-LDH/Ni3 S2 /NF composites have been successfully prepared on the nickel foam by combining the hydrothermal and electrodeposition methods. The C/NiMn-LDH/Ni3 S2 /NF electrode exhibits superior specific capacitance of 3490 mF cm −2 at 2 mA cm −2 . The two-electrode device assembled by C/NiMn-LDH/Ni3 S2 /NF and activated carbon shows an excellent specific energy of 64.46 Wh kg −1 at 1279.96 W kg −1 . Abstract: Due to the excellent ion insertion and exchange capacity, the layered double hydroxide (LDH) is considered to be an ideal electrode material for pseudocapacitor. However, the fast redox reaction of LDH always results in low power density and poor cycle stability. In this work, the C/NiMn-LDH/Ni3 S2 is successfully prepared on the nickel foam (NF) and exhibits excellent electrochemical performance. The specific capacitance of C/NiMn-LDH/Ni3 S2 /NF electrode could reach 3490 mF cm −2 at a current density of 2 mA cm −2 and retains 84.25% capacitance after 5000 continuous cycles. In addition, the two-electrode device assembled by C/NiMn-LDH/Ni3 S2 /NF and activated carbon (C/NiMn-LDH/Ni3 S2 /NF//AC) shows an excellent specific energy of 64.46 Wh kg −1 at 1279.96 W kg −1 . The extraordinary electrochemical performance is owing to the synergistic effect of the components.